Estimation of the Thermo-Physical Properties of Foods using Substances Contents in the Temperature Range of -40°C to +40°C - Kumar , Sanoj (Journal of Postharvest Technology, 2016)
An easy way to calculate thermal conductivity, specific heat, density and thermal diffusivity for foods using the percentage contents by classes of substances (water, proteins, fats, carbohydrates, fibers and ash) using the MS Excel program has been presented and a comparison has been made with the available method. The comparison shows that quadratic expressions of Choi and Okos (1986) method may be replaced with the developed models, which are using straight line equations. This work utilized the MS-Excel worksheet to develop models for the thermal properties of five food components (viz: fat; protein; carbohydrate; fiber; and ash), water and ice using Choi and Okos model to generate data. The results of correlation coefficients of the generated data using the developed models, show that: the values of R2 for: thermal conductivity ranges between 0.997 and 1; thermal diffusivity ranges between 0.991 and 1; specific heat ranges between 0.995 and 0.999; while that of density is 1. The R2value in the case of water and ice properties i.e., thermal conductivity, thermal diffusivity, specific heat and density are in the range of 0.918-1 and 0.981-1. This shows that the developed models may be used in the temperature ranges from -40°C to 40°C.